Are there gender differences in major depression and its response to antidepressants? - Scheibe, Susanne; Preuschhof, Claudia; Cristi, Carolina; Bagby, R.Michael (Journal of affective disorders, 2003)
Background: The prevalence of major depression for women is about twice that for men. This gender difference in prevalence rates has led to much research addressing gender differences in the presentation and features of major depression, and, to a lesser extent, research addressing gender differences in treatment response and personality. However, studies differ considerably in the population sampled, and findings vary significantly. In the current retrospective examination of data, we investigated all of these variables in one single sample of outpatients with major depression seen in a tertiary care centre. Methods: A sample of 139 men and 246 women with major depression receiving antidepressant treatment (SSRIs, TCAs, SNRIs, MAOIs, or RIMAs) in an outpatient setting were contrasted with regard to symptoms and severity of depression, course of illness, treatment response, and personality. Results: Women were found to experience more vegetative and atypical symptoms, anxiety, and anger than men, and to report higher severity of depression on self-report measures. Regarding personality, women scored higher on conscientiousness, the extraversion facet warmth, the openness facet feelings, and sociotropy. Effect sizes were small to moderate. No differences were found in the course of the illness and treatment response. Limitations: Findings are not generalizable to inpatient or community samples, and some of the gender differences may be accounted for by gender differences in treatment seeking behaviour. Conclusions: While men and women receiving antidepressant treatment show some gender differences in the psychopathology of major depression, these differences do not appear to translate into differences in response to antidepressants. Gender differences in personality appear less profound than in the average population, indicating the potential role of a certain personality type that predisposes individuals to develop clinical depression, independent of gender. Clinical relevance: The current examination underscores the role gender plays in the presentation and treatment of major depression.